The Chicken or the Egg: The Reciprocal Relationship Between Job Insecurity and Mental Health Complaints - Lopez-Bohle, S (Elsevier Inc., 2021)
To push the job insecurity literature forward, we bring together and simultaneously examine multiple theoretical frameworks to explain the direct job insecurity-mental health relationship and the reciprocal mental health-job insecurity relationship. Using 3-wave survey data, with a six-month time lag, from 1994 employees, we found that the stability of job insecurity from Time 1 to Time 2 was positively related to stress and social exchange mechanisms, as well as mental health complaints at Time 3. We also found that the stability of mental health complaints from Time 1 to Time 2 was positively related to the conservation of resources mechanism of absenteeism, as well as to perceptions of job insecurity at Time 3. Moreover, the stability of absenteeism over time was positively related to perceptions of job insecurity at Time 3. We discuss implications for the job insecurity literature, as well as make suggestions for future research and practical implications. © 2020 The Authors